Effectiveness of REDD programs in the protection of sui generis indigenous rights - Infante M., Paloma (Revista Tribuna Internacional, 2013)
The article focuses on the implementation of the United Nations Reducing Emission from Deforestation and Forest Degradation Program, hereinafter UN REDD and its effectiveness in the protection of sui generis indigenous rights, meaning those different from the property right but derived from it, especially, the rights over the territories, natural resources and environmental services. The paper will cover the interconnection between sui generis indigenous rights and REDD programs including the relevance of land tenure and the sui generis rights derived from it. As we will emphasize, REDD programs are not only focused in the reduction of carbon emissions. In fact, REDD plus programs include as a main objective the sustainable management of forests and the protection to forest dependent communities.